Serbia: Legal Solutions in Family Law to Existing Serious Demographic Problems - Kovaček Stanić, Gordana (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter analyses family policy in Serbia, in particular, youth and older adult policy and the institutional framework for the implementation of family policy. The chapter presents different measures that aim to empower and protect families, including family and work allowances, provisions in the pension and tax system, and provisions for family homes. In addition, family law solutions that regulate family relationships, such as the establishment of family status, property, and maintenance are also examined. The chapter also explores the legal framework for assisted reproductive technologies, including the different procedures that are and are not available in Serbia, such as surrogate motherhood, and the establishment of family status. It concludes that most of the measures have financial grounds, making them helpful for young people wanting to start a family. However, questions regarding the ultimate effects of these measures, and whether they are stimulating enough for couples to decide to have more children or whether overall social, economic, and political circumstances prevail in the decision-making on childbirth, are raised. Keywords: demography, allowance, family law instrument, assisted reproductive technology